Pengaruh Lokasi Usaha Terhadap Pendapatan Pedagang Menurut Perspektif Ekonomi Syariah: Studi Literatur Tentang Pengaruh Lokasi Terhadap Pendapatan Pedangan - Hajrah Hajrah; Askari Zakariah; Novita Novita (STIKes Ibnu Sina Ajibarang, 2024)
Income is the amount of money or goods received from other parties, as well as profits from industry, which are estimated based on the amount of money currently available. When selling both in the market and outside the market area, traders must have a strategy so that their merchandise is sold and the trader's income increases. So this research aims to determine the effect of business location on income according to a sharia economic perspective. The type of research used in this research is library research using 30 out of 50 references, where the data source is taken from Google Scholar. The approach used in this research is a qualitative approach with domain data analysis. The results of this research indicate that location has a significant influence on trader income. This is because the more strategic a location a trader chooses, the higher the income they will earn. If the location is also easy to reach, it will be easier for consumers to get what they want, as in Islamic teachings that if someone gives kindness to another person, that kindness will return to him.